ANALISIS SWOT PADA USAHA MIKRO KECIL MENENGAH SABLON (STUDI KASUS UMKM ONDERDIL SABLON, KOTA JAKARTA SELATAN, DKI JAKARTA) - Feriandy, Feriandy; Abdila, Kemil Pasya; Masrifah, Ifah (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
This thesis discusses the SWOT analysis of Screen Printing Parts SMEs in order to obtain the right marketing strategy. Screen Printing Parts is one of the MSMEs located in South Jakarta City, DKI Jakarta, which has been developing since 2017. Onderdil Sablon produces screen printing clothes and screen printing tools. Since starting his business, Onderdil Sablon have always been faced with various kinds of obstacles. The number of similar companies that have emerged makes it difficult for Onderdil Sablon to maintain their product position due to increasingly fierce industry competition. The condition of intense competition is a problem faced Onderdil Sablon. The purpose of this study was to determine the marketing strategy for UMKM Screen Printing Parts through SWOT analysis. In determining the marketing strategy, it is necessary to know the internal factors of strengths and weaknesses, as well as external factors of opportunities and threats. The strategy that can be applied, namely the ST strategy is a strategy that uses the strengths of the company to overcome threats or commonly called a diversification strategy.